2022
DOI: 10.1186/s12903-022-02167-5
|View full text |Cite
|
Sign up to set email alerts
|

PINK1 mediated mitophagy attenuates early apoptosis of gingival epithelial cells induced by high glucose

Abstract: Background Oxidative stress mediated by hyperglycemia damages cell-reparative processes such as mitophagy. Down-regulation of mitophagy is considered to be a susceptible factor for diabetes mellitus (DM) and its complications. However, the role of mitophagy in DM-associated periodontitis has not been fully elucidated. Apoptosis of human gingival epithelial cells (hGECs) is one of the representative events of DM-associated periodontitis. Thus, this study aimed to investigate PTEN-induced putativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A recent study shows that PINK1 inhibits oxidative stress-induced apoptosis by adjusting the expression of apoptosis related-genes Bax and Bcl-2 after the pretreatment of PDLSCs with antioxidants. 55 Zhu et al 56 Results revealed that the increased expression of pro-inflammatory factors and mtROS depended on the decreased expression levels of PINK1, parkin and LC3. Therefore, mitophagy may be a therapeutic target to mitigate cell death and inflammatory damage.…”
Section: Pten-induced Putative Kinase 1 (Pink1) Is An Autophagy-relatedmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study shows that PINK1 inhibits oxidative stress-induced apoptosis by adjusting the expression of apoptosis related-genes Bax and Bcl-2 after the pretreatment of PDLSCs with antioxidants. 55 Zhu et al 56 Results revealed that the increased expression of pro-inflammatory factors and mtROS depended on the decreased expression levels of PINK1, parkin and LC3. Therefore, mitophagy may be a therapeutic target to mitigate cell death and inflammatory damage.…”
Section: Pten-induced Putative Kinase 1 (Pink1) Is An Autophagy-relatedmentioning
confidence: 99%
“…A recent study shows that PINK1 inhibits oxidative stress‐induced apoptosis by adjusting the expression of apoptosis related‐genes Bax and Bcl‐2 after the pretreatment of PDLSCs with antioxidants 55 . Zhu et al 56 constructed a high glucose‐induced apoptosis model of human gingival epithelial cells. The rescue experiment verified that PINK1 regulated the expression level of apoptotic signal caspase 9, suggesting that PINK1/parkin‐mediated mitophagy protects diabetic periodontitis cells from apoptosis.…”
Section: Mitophagy and Periodontitismentioning
confidence: 99%
“…This partially explains how inflammation destroys the epithelial barrier while clearing bacteria. Also, GECs in diabetic periodontitis patients undergo apoptosis due to oxidative stress induced by high glucose, and PINK1-mediated mitophagy can attenuate this damage [63]. The downregulation of mitophagy is considered to be a predisposing factor for diabetes and its various complications.…”
Section: Gingival Epithelial Cellsmentioning
confidence: 99%